Framing languages and literacies : socially situated views and perspectives - Hawkins, Margaret R., 1953- (New York : Routledge, 2013)
"In this seminal volume leading language and literacy scholars clearly articulate and explicate major social perspectives and approaches in the fields of language and literacy studies. Each approach draws on distinct bodies of literature and traditions and uses distinct identifiers, labels, and constellations of concepts; each has been taken up across diverse global contexts and is used as rationale and guide for the design of research and of educational policies and practices. Authors discuss the genesis and historical trajectory of the approach with which they are associated; offer their unique perspectives, rationales, and engagements; and investigate implications for understanding language and literacy use in and out of schools. The premise of the book is that understanding concepts, perspectives and approaches requires knowing the context in which they were created, the rationale or purpose in creating them, and how they have been taken up and applied in communities of practice. Accessible yet theoretically rich, this volume is indispensible for researchers, students, and professionals across the fields of language and literacy studies"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Literacy -- Social aspects; English language -- Study and teaching -- Social aspects; Electronic books